Identification and characterization of planarian multinucleated cells in Schmidtea mediterranea using imaging flow cytometry - Dutta, Annasha; Samelak-Czajka, Anna; Trybus, Magdalena; Osuch, Marcin; Zaremba, Anastasiia; Jackowiak, Paulina (Frontiers in Cell and Developmental Biology, 2025)
Cellular polyploidy plays critical roles in both pathological and physiological processes. While extensively studied in organisms like Drosophila and zebrafish, and mammalian tissues such as the liver, kidney and heart, the existence of multinucleated polyploid cells in planarians, particularly asexual species, remains poorly understood. Here, we describe a novel approach combining imaging flow cytometry and fluorescence-activated cell sorting, to identify and characterize a stable population of presumed multinucleated cells in Schmidtea mediterranea under both regenerating and non-regenerating conditions. Insights into nuclearity, along with cell and nuclear size, suggest that these cells are formed through mechanisms involving cell fusion and/or endomitosis. Furthermore, analysis of marker gene expression patterns in the population containing multinucleated cells, upon neoblast depletion, suggests that they are likely undifferentiated. In addition, knockdown of the late epidermal progenitor marker Agat-1 followed by AGAT-1 custom antibody-based staining of cell populations indicates that the majority of MuNs are possibly late epidermal progenitor cells. Overall, the new findings presented here pave the way for further exploration into the biological significance of multinucleated cells in planarian regeneration and tissue maintenance.